Joyriding in Riyadh : oil, urbanism, and road revolt - Ménoret, Pascal, 1976-; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
Why do young Saudis, night after night, joyride and skid cars on Riyadh's avenues? Who are these 'drifters' who defy public order and private property? What drives their revolt? Based on four years of fieldwork in Riyadh, Pascal Menoret's Joyriding in Riyadh explores the social fabric of the city and connects it to Saudi Arabia's recent history. Car drifting emerged after Riyadh was planned, and oil became the main driver of the economy. For young rural migrants, it was a way to reclaim alienating and threatening urban spaces. For the Saudi state, it jeopardized its most basic operations: managing public spaces and enforcing law and order. A police crackdown soon targeted car drifting, feeding a nation-wide moral panic led by religious activists who framed youth culture as a public issue. This book retraces the politicization of Riyadh youth and shows that, far from being a marginal event, car drifting is embedded in the country's social violence and economic inequality.
List of maps -- List of figures -- A night with 'Ajib -- Repression and fieldwork -- City of the future -- The business of development -- Street terrorism -- Street politics -- Epilogue -- Bibliography -- Photo credits.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Petroleum industry and trade -- Saudi Arabia; Cities and towns -- Growth; Electronic books